CHANGES OF NONESSENTIAL TRACE ELEMENTS LEVELS IN WHOLE BLOOD OF END STAGE RENAL DISEASE ADULT PATIENTS - O. O. Makarov; E. O. Pisarev; B. S. Sheiman; M. V. Kulizkiy; D. V. Peretyatko; V. O. Vihor; M. G. Prodanchuk (Український Журнал Нефрології та Діалізу, 2017)
Aims: Accumulation of trace elements occurs in conditions of decreased or termination of kidneys functions. In some conditions increased trace elements can obtain toxic features. On other hand, researches are showing that concentration of some trace elements could be decreased in ERSD patients, too. The most important factor affecting trace element concentration in ERSD patient is the degree of renal failure and using of replacement therapy.